Choroideremia associated with choroidal neovascularization treated with intravitreal bevacizumab - Palejwala, Neal V (Dove Medical Press, 2014)
PURPOSE: To report a rare case of central vision loss in a patient with choroideremia. PATIENTS AND METHODS: A retrospective, interventional case report. RESULTS: A 13-year-old male with history of choroideremia presented with subacute loss of central acuity in his left eye. Examination and diagnostic testing revealed subretinal fibrosis secondary to a choroidal neovascular membrane (CNVM). A trial of anti-vascular endothelial growth factor (VEGF) therapy with the injection of intravitreal bevacizumab was attempted. Mild improvements in acuity and anatomy were noted. CONCLUSION: Choroideremia is a rare hereditary choroidal dystrophy that predominantly affects males in the first and second decades of life. Visual acuity is usually spared until later in life. CNVM is a rare manifestation of choroideremia with only a handful of case reports presented in the literature. This case is unique in that it is the first reported case that received treatment with intravitreal anti-VEGF therapy.